EFFECTS OF SOLID WASTE MANAGEMENT ON THE QUALITY OF LIFE OF PEOPLE IN BIRNIN KEBBI METROPOLIS - Mainasara, Nura; Dodo, Felix Emmanuel (FUDMA Journal of Earth and Environmental Sciences, 2024)
The study examines the effects of solid waste management on the quality of life of people in Birnin Kebbi Metropolises. The study administered 100 structured questionnaires to collect information from different communities. Additionally, an interview was carried out with officials of the state environmental agencies involved in solid waste management to confirm some of the respondents' information. The study used both chi-square and descriptive statistics for data analysis. The results showed that domestic sources of waste account for roughly 45% of all solid waste in Birnin-Kebbi Metropolises, followed by business sources at 25% and agricultural sources at 19%, with the remaining 11% coming from other sources. The chi-square results state a significant correlation between solid waste management and the quality of life of the people in the Birnin-Kebbi metropolitan areas. This implies that poor solid waste management significantly lowers the quality of life of people in Birnin-Kebbi. Based on the results, the government should establish a well-equipped task force to oversee the careless disposal of waste to preserve environmental cleanliness and prevent the spread of diseases throughout the city.